EFEKTIVITAS PROGRAM BANTUAN PEMERINTAH BAGI USAHA MIKRO DI KABUPATEN PONOROGO - Nida Faizatul Mustofa; Ratna Yunita (Institut Agama Islam Negeri Ponorogo, 2021)
One of the government's efforts to overcome the COVID-19 pandemic which has affected several sectors, one of which is the economic sector, is by launching the Government Assistance for Micro Enterprises (BPUM) program. This BPUM aims to support and maintain the sustainability of micro-enterprises as well as a form of saving the national economy during the COVID-19 pandemic that threatens the national economy. This program was only issued during the 2019 covid pandemic, so it is still very new and there is still not much research on this program. The problem in this research is how the effectiveness of achieving the objectives, integration, and adaptation of the Government Assistance for Micro Enterprises (BPUM) program is. This research program uses a field method using a qualitative approach and uses a descriptive type of research. The results of the research are, firstly, the measure of achieving the goals has not been effective because the targets have not been fully accurate and the management of aid funds is still not in accordance with the objectives. Second, the integration measure has not been effective because there is no socialization from related parties to the prospective recipients of the BPUM program. And third, the adaptation measure has not been effective either because the implementing party did not conduct monitoring before or after receiving this assistance program. Salah satu upaya pemerintah dalam mengatasi pendemi covid-19 yang mengakibatkan beberapa sektor terdampak, salah satunya sektor perekonomian yaitu dengan mencanangkan program Bantuan Pemerintah bagi Usaha Mikro (BPUM). BPUM ini bertujuan untuk mendukung dan menjaga keberlangsungan usaha mikro serta sebagai bentuk penyelamatan ekonomi Nasional pada masa pandemi covid-19 yang mengancam perekonomian Nasional. Program ini baru dikeluarkan pada saat pandemi covid tahun 2019, sehingga masih sangat baru dan masih belum banyak penelitan tentang program ini. Permasalahan dalam penelitian ini adalah bagaimana efektivitas pencapaian tujuan, integrasi, dan adaptasi program Bantuan Pemerintah bagi Usaha Mikro (BPUM). Program Penelitian ini menggunakan metode lapangan dengan menggunakan pendekatan kualitatif dan menggunakan jenis penelitian deskriptif. Hasil penelitian yaitu, pertama pada ukuran pencapaian tujuan belum efektif dikarenakan target sasaran belum sepenuhnya tepat serta pengelolaan dana bantuan yang masih belum sesuai dengan tujuan. Kedua, pada ukuran integrasi belum efektif karena tidak adanya sosialisasi dari pihak terkait terhadap calon penerima program BPUM. Dan ketiga, pada ukuran adaptasi juga belum efektif karena pihak pelaksana tidak melakukan pemantauan sebelum maupun sesudah menerima program bantuan ini.